Sri Lankan Youth and their Exposure to Computer Literacy - de Silva, W. Indralal; Kodikara, Pamoda; Somarathne, Ruwani (My University, 2014)
The general objective of this study is to elucidate the level of computer literacy and exposure to the internet among Sri Lankan youth aged 15-29 years based on their main economic activity. In order to achieve this objective a two-layered data collection approach was adopted as the overall methodology of the 2009 National Youth Survey. Quantitative data was collected from a randomly selected sample of 3000 households covering 22 districts out of a total of 25 districts. The conclusions reached from this study were that out of 2921 respondents 57% of youth were computer literate. Out of the 18-24 age group 65% could manage basic functions of the computer as opposed to the 25-29 year olds where only a 43% demonstrated knowledge in computer usage. This indicates that the older group had a lesser opportunity at gaining computer knowledge, which is a fairly recent development in Sri Lanka. It was also revealed that 33% of youth who have a basic knowledge in computer usage have their own computers while 33% have used the internet. In terms of usage and frequency out of the 57% youth who are computer literate 50% use their computers on a daily/weekly basis.
Keywords: Economy; Economic Development; Globalization; ICT; IT Literacy; Knowledge